Rectal Inflammatory Myoglandular Polyp with Osseous Metaplasia in a Child. (4th March 2022) - Mitra, Suvradeep; Sable, Mukund; Sahoo, Subrat Kumar; Mohanty, Manoj Kumar
Abstract: Background : Inflammatory myoglandular polyp (IMGP) combines the histopathological features of juvenile polyp and Peutz-Jegher's polyp. Osseous metaplasia can be occasionally seen in various benign, adenomatous, and malignant polyps. Case report: A nine-year-old girl with hematochezia had a rectal polyp with histological features of IMGP with additional stromal osseous metaplasia. Conclusion: Benign osseous metaplasia can be found in IMGP.